Mystical Luminosity Experience : An Initiation of a Construct Grounded in Phenomenology - Dinsmore, Jonathan, (Brill Research Perspectives in Humanities and Social Sciences ;, 2024)
Light of a divine or transcendent nature is widely revered in various religious and mystical traditions around the world, and luminosity with mystical qualities such as love, bliss, peace, and noetic realization is also frequently reported by contemporary experiencers. Despite being described as a profoundly significant, sacred, and transformative experience, mystical luminosity has received relatively little attention in modern scholarship and scientific study, and has only been examined empirically within isolated contexts, such as NDEs or contemplative practices. This study examines the phenomenology which binds mystical luminosity across various experiential contexts to construct a phenomenologically grounded theoretical model. A three-part mixed methods investigation using a new mystical luminosity experience scale based on this model is then summarized, with findings generally supporting and further clarifying the model.